2013
DOI: 10.1007/s10354-012-0173-1
|View full text |Cite
|
Sign up to set email alerts
|

Atypical fibroxanthoma—a diagnosis of exclusion!

Abstract: Fibrohistiocytic tumors of the skin comprise a large range of lesions. One such tumor is the atypical fibroxanthoma (AFX), which is widely considered as a "pseudomalignant" tumor. It is derived from fibroblasts and expresses a variety of histiocytic markers. We present a case of AFX, localized in the right temporal region of the scalp, successfully treated with surgical excision. Immunohistochemical staining helps differentiate this tumor from others in the clinical differential diagnosis, including malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…There were 218 cases from 10 eligible studies citing MMS as the main mode of treatment (Table ). Compiled recurrence rates were 4.6%, and metastasis rates were 3.2%.…”
Section: Resultsmentioning
confidence: 99%
“…There were 218 cases from 10 eligible studies citing MMS as the main mode of treatment (Table ). Compiled recurrence rates were 4.6%, and metastasis rates were 3.2%.…”
Section: Resultsmentioning
confidence: 99%
“…AFX has a mesenchymal origin (fibroblastic, fibrohistiocytic or myofibroblastic nature), that is, it may be derived from fibroblasts, fibrohistiocytes or myofibroblasts [59,67,81]. In 1973, VargasCortes et al suggested that AFX may arise from the tissue histiocytes.…”
Section: Molecular Pathology Of Afxmentioning
confidence: 97%
“…[3] Current opinions and evidence of clinical and diagnostic differences between AFX and MFH are pointed to consider AFX as a distinct entity with MFH/UPS. [45] The AFX generally arises on the skin damaged by radiation, particularly in solar phototype subjects below. Often it is localized in areas such as head and neck of elderly patients surrounded by areas with apparent actinic damage; moreover, it may localize on burn scars.…”
Section: Discussionmentioning
confidence: 99%